The Impact of the Interest Rate Change on Bank Stock Returns - WANG, NIANXUAN (2012)
In this paper, existing theories of to support the relationship between bank stock return and interest rate will be introduced firstly. Based on the sample of nine year daily bank stock return in the U.S stock market, the influence from the market stock index, short-term and long-term interest rate change are all examined. To get a comparable and more accurate result, ARCH and GARCH estimation methods are used to correct the volatility clustering in OLS estimation. To get further research findings, the banks are classified based on the total asset. Both the market stock index and interest rate are found to have significant impact on the bank stock return. Note that the influence from interest rate differs in different situation, while the influence from the market stock index keeps consistent.